2013
DOI: 10.1111/ppa.12095
|View full text |Cite
|
Sign up to set email alerts
|

The effects of co‐infection by different Potato virus Y (PVY) isolates on virus concentration in solanaceous hosts and efficiency of transmission

Abstract: The influence of co‐infection on concentration and accumulation of genetically different isolates of Potato virus Y (PVY) in potato and tobacco plants and the efficiency of transmission by Myzus persicae of PVY isolates from doubly versus singly infected plants were evaluated. The vector ability to simultaneously transmit two virus isolates was examined. Eight PVY isolates represented three strain groups: PVYO (pathotype and serotype O), PVYNW (pathotype N and serotype O), and PVYNTN (pathotype and serotype N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…Therefore, an aphid need not acquire both strains from one source plant in order to transmit multiple viruses. In fact, acquisition and subsequent transmission of both virus strains from a mixedinfected plant is not generally efficient (Srinivasan et al, 2012;Syller & Grupa, 2014) and mixed-infected plants are not abundant in the field (Gray et al, 2010). Our results suggest that mixed-infected plants would more likely be generated in the field via inoculation by multiple aphids that have fed on plants infected with different strains than by single aphids probing multiple plants singly (Fig.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Therefore, an aphid need not acquire both strains from one source plant in order to transmit multiple viruses. In fact, acquisition and subsequent transmission of both virus strains from a mixedinfected plant is not generally efficient (Srinivasan et al, 2012;Syller & Grupa, 2014) and mixed-infected plants are not abundant in the field (Gray et al, 2010). Our results suggest that mixed-infected plants would more likely be generated in the field via inoculation by multiple aphids that have fed on plants infected with different strains than by single aphids probing multiple plants singly (Fig.…”
mentioning
confidence: 67%
“…Multiple studies report that PVY NTN is more efficiently transmitted by aphid vectors than other strains (Cervantes & Alvarez, 2011;Srinivasan et al, 2012), although contrasting findings have also been published (Davis et al, 2005;Verbeek et al, 2010). In mixed strain infections, PVY NTN seems to outcompete other PVY strains in potato, which may contribute to enhanced transmission efficiency (Cervantes & Alvarez, 2011;Syller & Grupa, 2014). During surveys of US seed potatoes (Gray et al, 2010), PVY NTN was often found in the same field and occasionally in the same plant with PVY O .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For total RNA isolation and cDNA synthesis, the procedure described by Syller and Grupa () was employed. The RT‐PCR was performed as described by Xu et al.…”
Section: Methodsmentioning
confidence: 99%
“…(), Srinivasan et al . () and Syller and Grupa (), can be explained as proposed above, and illustrated in Fig. .…”
Section: Simultaneous Virus Transmission By Aphidsmentioning
confidence: 99%